Partial trisomy 15: a rare occurrence - Gandhi, Prachi; Malik, Sushma; Subramanian, Sharan; Wade, Poonam; Saxena, Shruti; Lichade, Vinaya (International Journal of Contemporary Pediatrics, 2019)
Partial trisomy 15q is a very rare entity and most of them are characterized by duplication of regions 15q21-15q26.3. This duplication is frequently associated with deletions in another chromosome resulting in unbalanced translocations. Authors report here, a rare case of partial trisomy 15, with breakpoints between 15q11.1 to q23, probably the first reported case with these breakpoints. Irrespective of the breakpoints, the phenotypic features are consistent in all affected cases and predominantly consist of craniofacial anomalies. In addition, finger abnormalities, very short neck, skeletal malformations and congenital heart disease may be present. Our neonate had typical dysmorphic features of arachnocamptodactyly, narrow face, large prominent, nose with broad nasal bridge, long philtrum, pointed chin, short neck, and low set deformed ears. Neonates’ cytogenetic analysis revealed additional chromosomal material on the long arm of the chromosome 15 from q11.1 to q23.1, which was suggestive of partial trisomy of chromosome 15. Most cases reported have had a stormy clinical course, however, our proband had only mild respiratory distress at birth and she was discharged in a few days.